2013
DOI: 10.1051/fruits/2013075
|View full text |Cite
|
Sign up to set email alerts
|

Resource use and GHG emissions of eight tropical fruit species cultivated in Colombia

Abstract: -Introduction. The cultivation of high-value fruit species is a profitable agricultural activity in many tropical countries; however, intensive fruit cultivation may depend on high amounts of external inputs. The objective of our study was to quantify and compare the resource use during the cultivation of eight tropical fruit species (Rubus glaucus, Solanum quitoense, Passiflora edulis, Cyphomandra betacea, Physalis peruviana, Ananas comosus, Persea americana and Mangifera indica) commonly cultivated in Colomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…In Ocati, this value increased to 6 kg CO 2 eq per kg in convectional orchards, mainly due to transportation. For Colombian organic crops (Frohmann et al 2015 ; Graefe et al 2013 ; Perez 2012 ), CFs between 4.76 and 7.11 kg CO 2 eq per kg have been reported, values considerably higher than the CF obtained in this work for the Spanish organic gooseberry crop. This is even more noteworthy if we take into account that the yearly productivity in the cape gooseberry crop here analysed was 1600 kg/ha, much lower than productivities above 10,000 kg/ha reported in Colombia.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…In Ocati, this value increased to 6 kg CO 2 eq per kg in convectional orchards, mainly due to transportation. For Colombian organic crops (Frohmann et al 2015 ; Graefe et al 2013 ; Perez 2012 ), CFs between 4.76 and 7.11 kg CO 2 eq per kg have been reported, values considerably higher than the CF obtained in this work for the Spanish organic gooseberry crop. This is even more noteworthy if we take into account that the yearly productivity in the cape gooseberry crop here analysed was 1600 kg/ha, much lower than productivities above 10,000 kg/ha reported in Colombia.…”
Section: Resultscontrasting
confidence: 55%
“…per kg of fruit. Different authors (Frohmann et al 2015 ; Graefe et al 2013 ; Perez 2012 ) have carried out diverse studies on calculating the CF of cape gooseberry production in various regions of Colombia. In Novacampo, a value of 5.20 kg CO 2 eq per kg of fruit was obtained, being consumption of fertilisers and packaging the most impacting subsystems.…”
Section: Resultsmentioning
confidence: 99%
“…The carbon balance (CB), the difference between total carbon output and total carbon input, and the carbon efficiency (CE) of the different cropping systems were calculated according to Lal [49]:…”
Section: Greenhouse Gases Emissionsmentioning
confidence: 99%
“…This value is lower than those published for orange crop (1.42 kg of CO 2 eq/kg of orange [19], coconut fruit (2.4-6, kg of CO 2 eq/kg of coconut), and peanuts (1.8-3 kg of CO 2 eq/kg of peanuts) [27]. For the cultivation of lulo, pineapple, and avocado, the carbon footprint ranges between 1.7 to 2.4 kg of CO 2 eq per kilogram of fruit [28]. On the other hand, Barrera-Ramírez et al [29] reported 3.18, 0.042, and 1.3 kg of CO 2 eq for 1 kg of coffee, sugar cane, and cocoa, respectively, grown in Colombia.…”
Section: Environmental Resultsmentioning
confidence: 99%